POLITICAL JOURNALISM BETWEEN NEWS AND OPINION: a comparative study of the 2018 Brazilian presidential elections - Santos, Deivison Henrique de Freitas; Marques, Francisco Paulo Jamil; Fontes, Giulia Sbaraini (Brazilian journalism research, 2020)
This article compares editorial and news agendas considering O Estado de S. Paulo, Folha de S. Paulo, and O Globo newspapers during the second round of the 2018 Brazilian presidential election. We study to what extent the convergence between both agendas discloses some of the political interests sponsored by news organizations. By using content analysis, we examined the thematic convergence between 144 editorials and news. The hypotheses are: H1) The news and opinion sections within each newspaper converge thematically, indicating a political instrumentalization of the journalistic practices; H2) Newspapers differ from each other when considering the topics covered in their editorials, which is not the case when their main cover stories are at stake. The results indicate that the newspapers do not present a strong convergence within their intern sections. However, there is similarity between the opinionated agenda between the news organizations, which doesn’t happen with the news coverage. O objetivo deste trabalho é comparar as agendas editorial e noticiosa dos jornais O Estado de S. Paulo, Folha de S.Paulo e O Globo durante o segundo turno da eleição presidencial de 2018. Pretende-se, especificamente, compreender em que medida as semelhanças entre as referidas agendas podem revelar, pelo menos em parte, os interesses políticos das publicações. A análise de conteúdo de 144 textos permitiu observar o nível de sintonia temática entre as peças jornalísticas. As hipóteses são: H1) As seções noticiosa e opinativa internas a cada jornal convergem tematicamente, indicando instrumentalização político-eleitoral da atividade jornalística; H2) Os jornais divergem entre si quando são diretamente comparados os temas abordados em seus editoriais, o que não ocorre em suas principais matérias de capa. Descobriu-se que os periódicos não apresentam convergências expressivas em suas seções internas. Todavia, há convergência entre as agendas opinativas dos jornais, diferentemente do que acontece em suas notícias. Este artículo compara las agendas editoriales y de noticias de O Estado de S. Paulo, Folha de S.Paulo y O Globo durante la segunda vuelta de las elecciones presidenciales brasileñas de 2018, buscando identificar si hay similitudes entre ellas. El análisis de contenido de 144 editoriales y noticias nos permitió observar la armonía temática entre los textos. Las hipótesis son: H1) Las secciones de noticias y opinión dentro de cada periódico convergen temáticamente, lo que indica la instrumentalización político-electoral de la actividad periodística; H2) Los periódicos difieren entre sí cuando los temas de sus editoriales se comparan directamente, lo cual no es el caso en sus principales portadas. Se encontró que no hay convergencias temáticas expresivas en las secciones de cada publicación. Sin embargo, los resultados indican cierta convergencia entre las agendas de opinión de los periódicos, lo que no se percibe con la misma intensidad en las noticias.